Last Shift (Fields)
The Romanian authorities submitted a detailed table with viability scores for each production unit. The results of the ranking outlined that Paroseni, Uricani and Petrila production units do not have viable economic perspectives and need to be included in the closure plan’ (State aid SA. 33033 — Romania — National Hard Coal Company Petroşani, 22nd November 2012) On 26th November 2012, Valea Jiului (the National Society of Closing Coal Mines), was established with the sole purpose of closing down three coal mines (S.M. Paroseni, S.M. Petrila and S.M. Uricani) that were perceived as uneconomical and unreliable.. Last Shift is a photographic documentary of the last few months of mining activity in each of the three mines. The collection of images aims to raise awareness of the coal mining industry in Romania, and the proposed closures. The project shares a similar topic to Sebastiao Salgado’s Workers project of the 1990s. However, Salgado’s images are often criticized for being too aestheticized, exploiting human misery and showing the effects of heavy toil in a romantic way, whilst the purpose of Last Shift is to show the miners as individuals in a dignified manner, focusing on the humanity of each subject.